Enhance the robustness of secure Rijndael key expansion function based on increment confusion and diffusion bits - Hussien, Hassan Mansour; Muda, Zaiton; Md. Yasin, Sharifah (School of Computing, UUM College of Arts and Sciences, 2017)
Symmetric block ciphers are the most widely utilized cryptographic primitives. Since block ciphers provide privacy; block ciphers are hence used as core components for the construction of hash functions such as one-way compression functions and pseudorandom number generators, all as part of several cryptographic protocols, etc. These days the most common block cipher is the AES Rijndael, which is used as a standard of symmetric encryption in many countries. Several studies have shown a theoretical attack exploiting the AES key expansion algorithm which allows significant reduction in the complexity time to break the cipher, compared to the brute force attack. The arrack in the related-key model and the long biclique with a meet in the middle attacks in the secret-key model are applied on the AES because of the weak key expansion function. Authors of AES accepted that the key expansion function of Rijndael is comparatively weak. Confusion and diffusion are two properties of the operation a secure cipher. Therefore, although the two properties within the substitution-permutation construct are only applied to state the transformation round function of the Rijndael algorithm, but there is no other strong security for the key expansion function. This article, hence presents a method to improve the Key Schedule of the Rijndael cipher in order to maintain the requirement of bits confusion and diffusion properties besides making the cipher more resistance to differential cryptanalysis.